1979
DOI: 10.1128/jb.137.2.1056-1058.1979
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the membrane composition of Spiroplasma citri and the corn stunt Spiroplasma

Abstract: Components of membranes isolated from Spiroplasma citri and corn stunt spiroplasma grown at 28°C were analyzed. On a protein basis, lipid phosphorus was lower and cholesterol was higher in S. citri. Only minor differences between the two species were found in fatty acid composition, reduced nicotinamide adenine dinucleotide diaphorase, and adenosine triphosphatase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
2
0

Year Published

1979
1979
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 11 publications
(11 reference statements)
2
2
0
Order By: Relevance
“…The higher incorporation of palmitate as compared with oleate noticed in ouir study was reported previously for S. citri (8,12,13). Moreover, we have demonstrated that in S. floricola, the major de novo synthesized phospholipid, PG, shows an unusual distribution of fatty acids.…”
Section: Spiroplasma Membrane Lipidssupporting
confidence: 81%
See 3 more Smart Citations
“…The higher incorporation of palmitate as compared with oleate noticed in ouir study was reported previously for S. citri (8,12,13). Moreover, we have demonstrated that in S. floricola, the major de novo synthesized phospholipid, PG, shows an unusual distribution of fatty acids.…”
Section: Spiroplasma Membrane Lipidssupporting
confidence: 81%
“…BC3 to S. citri (Tables 1 and 2) is in line with the marked genetic relatedness (more than 60% DNA homology) of these two organisms (3). Similarly, the lipid composition of S. citri was found to be almost identical to that of the corn-stunt spiroplasma (13,14), an organism showing ca. 50% DNA homology with S. citri (3).…”
Section: Spiroplasma Membrane Lipidssupporting
confidence: 70%
See 2 more Smart Citations